Association with Membrane Protrusions Makes ErbB2 an Internalization-resistant Receptor - Hommelgaard, Anette M. (The American Society for Cell Biology, 2004)
In contrast to the epidermal growth factor (EGF) receptor, ErbB2 is known to remain at the plasma membrane after ligand binding and dimerization. However, why ErbB2 is not efficiently down-regulated has remained elusive. Basically, two possibilities exist: ErbB2 is internalization resistant or it is efficiently recycled after internalization. By a combination of confocal microscopy, immunogold labeling electron microscopy, and biochemical techniques we show that ErbB2 is preferentially associated with membrane protrusions. Moreover, it is efficiently excluded from clathrin-coated pits and is not seen in transferrin receptor-containing endosomes. This pattern is not changed after binding of EGF, heregulin, or herceptin. The exclusion from coated pits is so pronounced that it cannot just be explained by lack of an internalization signal. Although ErbB2 is a raft-associated protein, the localization of ErbB2 to protrusions is not a result of raft binding. Also, an intact actin cytoskeleton is not required for keeping ErbB2 away from coated pits. However, after efficient cross-linking, ErbB2 is removed from protrusions to occur on the bulk membrane, in coated pits, and in endosomes. These data show that ErbB2 is a remarkably internalization-resistant receptor and suggest that the mechanism underlying the firm association of ErbB2 with protrusions also is the reason for this resistance.